2020
DOI: 10.1108/jmtm-03-2020-0087
|View full text |Cite
|
Sign up to set email alerts
|

Organizational adoption of 3D printing technology: a semisystematic literature review

Abstract: PurposeThree-dimensional (3D) printing (3DP) offers a promising value proposition across multiple manufacturing industries. Despite the variety of production benefits the technology entails, its rate of adoption is still low compared to industry forecasts. In face of this challenge, industry as well as academia requires more information and guidance. This review aims to examine the characteristics of the existing body of research on the organizational adoption of 3DP as well as its underlying theoretical conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 57 publications
(91 reference statements)
0
15
0
Order By: Relevance
“…However, the obstacles are not clearly distinguished and the mechanism of adjusting the culture and strategy is rather abstract. In other studies, internal upper management support was found to a prominent factor (Chung and Choi, 2018;Lu et al, 2018;Mohtaramzadeh et al, 2018;Maali et al, 2020;Ukobitz, 2020). Furthermore, awareness of the state of affairs in the organization's external environment was found to be essential (Mohtaramzadeh et al, 2018;Vaishnavi et al, 2019).…”
Section: Existing Literaturementioning
confidence: 71%
“…However, the obstacles are not clearly distinguished and the mechanism of adjusting the culture and strategy is rather abstract. In other studies, internal upper management support was found to a prominent factor (Chung and Choi, 2018;Lu et al, 2018;Mohtaramzadeh et al, 2018;Maali et al, 2020;Ukobitz, 2020). Furthermore, awareness of the state of affairs in the organization's external environment was found to be essential (Mohtaramzadeh et al, 2018;Vaishnavi et al, 2019).…”
Section: Existing Literaturementioning
confidence: 71%
“…The main goal of this study was to generate new insights into how AM adoption takes place when adopted in the production value chains of companies that do not invest in AM machines and why AM is adopted into the value chain. This study contributes to the knowledge on the adoption of AM through the value-driven potential of AM and answers the call for studies to illustrate successful cases of AM adoption (Luomaranta and Martinsuo, 2020;Rylands et al, 2016;Ukobitz, 2021). We explored companies that cooperate in the value chain to generate new opportunities and analyzed innovation projects as platforms that enable the companies to benefit from each other when identifying value-adding applications and establishing new supply chains.…”
Section: Discussionmentioning
confidence: 85%
“…For the large-scale adoption of AM, AM concepts, products and processes need to be broadly accepted in the production value chain. Case studies of successful AM adoption have been called for (Luomaranta and Martinsuo, 2020; Ukobitz, 2021) to overcome managers' AM technology trust issues and further advance the adoption of AM. Our multiple-case study generated new knowledge on application recognition and interorganizational cooperation during innovation projects when adopting AM in companies' production value chains.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations